2002
DOI: 10.1262/jrd.48.189
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Cryopreserved and Vitrified Embryos and Fertility after Direct Transfer in Ewes.

Abstract: Abstract. The present study investigated the in vitro viability of cryopreserved-thawed ovine embryos by three methods, slow freezing (ethylene glycol (EG)-3 step method), freezing for direct transfer (Direct method) and vitrification (Experiment 1), and the in vivo viability by two transfer methods, direct ET (d-ET) and stepwise ET (s-ET), for the Direct method and vitrified embryos, respectively (Experiment 2). In vivo produced embryos (morula and blastocyst) were recovered from 79 superovulated and artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
3
1
Order By: Relevance
“…The loading constructions of the heat-pulled straw for direct transfer to ewes. result (7.9%) was lower than that of our previous study [1] using the stepwise method (40.0%). It has been reported that lambing results were not significantly different between the direct and stepwise methods [4,12].…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…The loading constructions of the heat-pulled straw for direct transfer to ewes. result (7.9%) was lower than that of our previous study [1] using the stepwise method (40.0%). It has been reported that lambing results were not significantly different between the direct and stepwise methods [4,12].…”
Section: Discussioncontrasting
confidence: 81%
“…In our previous study [1], viability of frozenthawed embryos by the slow freezing method after direct transfer (18.8%) was similar to that after in vitro development (12.8%). However, the influence on the viability after the transfer could not be clarified in this study, because the in vitro viability after cultivation of the embryos ranked as poor before vitrification was 12.5% (unpublished data), and the poor-ranked embryos were not transferred.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Meanwhile, to simplify the thawing and transferring procedure and make it more suitable for field use, some researchers have examined the feasibility of in-straw rehydration and direct transfer in the bovine [7], rabbit [8], ovine [9,10] and equine [11]. One feature of this thawing procedure is in-straw dilution, embryo thawing, and direct transfer of the thawed embryos.…”
mentioning
confidence: 99%